Al-Cu periodic laminated gradient composite material and preparation method thereof
Through the design of Al-Cu periodic laminated gradient composite materials combined with casting method combined with the preparation method of low temperature sintering process, the problems of low interface bonding strength and excessive intermetallic compound generation in traditional Al-Cu gradient flyers are solved, and the uniformity of gradient structure and interface bonding strength are improved, meeting the dynamic response research needs under high strain rate and high pressure conditions.
Patent Information
- Application Number
- CN202510126495.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-05-09
AI Technical Summary
The traditional Al-Cu gradient flysheet preparation method has problems such as low interface bonding strength, excessive generation of intermetallic compounds, poor interlayer flatness and low density, which affects dynamic loading stability.
The design of Al-Cu periodic laminated gradient composite material was adopted, and the Al and Cu casting sheets were prepared by casting method, and the gradient structure was formed according to the periodic laminated structure. Finally, it was prepared under low-temperature sintering conditions to reduce the formation of intermetallic compounds and improve the interface binding strength.
The uniformity of the gradient structure, the improvement of interface bonding strength, the reduction of intermetallic compound content, the improvement of interlayer flatness and density are achieved, and the research needs of dynamic responses under high strain rate and high pressure conditions are met.
Smart Images

Figure HDA0005260030120000011 
Figure HDA0005260030120000012 
Figure HDA0005260030120000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional gradient materials, and in particular relates to an Al-Cu periodic laminated gradient composite material and a preparation method thereof. Background Art
[0002] In dynamic loading experiments, the graded density impactor (GDI) is an important tool for achieving quasi-isentropic loading. The design of GDI requires precise control of the propagation of stress waves during the impact process, so as to achieve controllability of the stress and strain rate of the loaded sample. At present, the preparation of gradient flyers is mainly divided into two structures: laminated type and gradient type. Among them, the traditional laminated gradient flyer is usually composed of metal and metal, metal and ceramic materials with significant density differences, such as Al / W, Al / Cu or Al / Ta, etc. These materials are formed into a periodic structure by mechanical lamination, welding or high-temperature sintering. This type of flyer is widely used in high-precision dynamic loading experiments due to its flexible design and convenient density control. However, the preparation method of the traditional laminated flyer relies on high-temperature sintering or welding, which easily generates excessive intermetallic compounds at the interface. The hard and brittle characteristics of these compounds significantly reduce the bonding strength of the interface, thereby affecting the dynamic loading stability of the gradient flyer.
[0003] At present, the existing Al-Cu gradient flyers mostly adopt a gradient structure, that is, a gradient material with continuous density change is prepared by powder metallurgy or laser additive manufacturing. However, this type of structure has certain defects. First, the density gradient of the gradient material needs to be achieved by preparing a variety of powder materials with different ratios, but local density unevenness is prone to occur in actual preparation, resulting in a decrease in the accuracy of the loading waveform and a complicated process. Secondly, the interface transition of the gradient structure is slow, and grain boundary defects are easily generated, making the interface bonding strength lower than that of the laminated flyer. Finally, in high strain rate loading, the wave impedance distribution of the gradient structure is not clear enough, which reduces the propagation efficiency of the stress wave, and the dynamic response shows a certain hysteresis. Summary of the invention
[0004] The purpose of the present invention is to provide an Al-Cu periodic laminated gradient composite material and a preparation method thereof. The gradient composite material has the characteristics of uniform gradient structure, high interface bonding strength, low intermetallic compound content, high interlayer flatness and high density, which can meet the research needs of material dynamic response under high strain rate and high pressure conditions.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] Provided is an Al-Cu periodic laminated gradient composite material, which comprises n Al-Cu composite layers and a pure copper layer of the same thickness in sequence, wherein:
[0007] The Al-Cu composite layer includes an Al layer and a Cu layer in sequence; and from the first Al-Cu composite layer to the nth Al-Cu composite layer, the thickness gradient of the Al layer decreases gradually, and the thickness gradient of the Cu layer increases gradually.
[0008] According to the above scheme, n is 5-20.
[0009] According to the above scheme, in the first Al-Cu composite layer, the thickness ratio of the Al layer to the Cu layer is 25-28:1, and in the last Al-Cu composite layer, the thickness ratio of the Al layer to the Cu layer is 1:25-28.
[0010] According to the above scheme, the thickness of a single Al-Cu composite layer is 130-170 μm, and the thickness of the pure copper layer is 300-1350 μm.
[0011] According to the above scheme, the total thickness of the Al-Cu periodic laminated gradient composite material is 2000-4750 μm.
[0012] According to the above scheme, in the n-layer Al-Cu composite layer, the thickness of the Al layer decreases by 9 to 13 μm per layer, and the thickness of the Cu layer increases by 9 to 13 μm per layer.
[0013] According to the above scheme, the Al-Cu periodic laminated gradient composite material is prepared by using a tape casting method to obtain Al and Cu tape-cast sheets respectively, and then according to the structural design of the Al-Cu periodic laminated gradient composite material, the obtained Al and Cu tape-cast sheets are overlapped with each other to form a gradient structure stack, and finally the binder is removed and hot-pressed and sintered under 290-300MPa and 485-500°C to obtain the composite material.
[0014] Preferably, the hot pressing sintering time is 2 to 3 hours.
[0015] Preferably, the temperature is first raised to 280-320° C. and kept for 25-40 min, then the pressure is raised to 290-300 MPa, and finally the temperature is further raised to 485-500° C. and kept for 2-3 h.
[0016] A method for preparing the Al-Cu periodic laminate gradient composite material is provided, comprising the following steps:
[0017] Step 1: Prepare Al and Cu cast films respectively by tape casting method, and then cut and demold to obtain the required Al and Cu cast sheets;
[0018] Step 2: According to the structural design of the Al-Cu periodic laminated gradient composite material, the Al and Cu tape-cast sheets obtained in the multilayer step 1 are overlapped to form a gradient structure laminate, and then the binder is removed to obtain a gradient composite material blank;
[0019] Step 3: The gradient composite material blank obtained in step 2 is pressed as a whole, and then hot-pressed and sintered at 290-300 MPa and 485-500° C. to finally obtain an Al-Cu periodic laminated gradient composite material.
[0020] According to the above scheme, in step 1, the specific process of preparing Al and Cu cast sheets by tape casting is as follows:
[0021] 1) preparing a tape casting slurry containing metal powder, solvent, dispersant, binder and plasticizer by ball milling, wherein the metal powder is aluminum powder or copper powder;
[0022] 2) The casting slurry obtained in step 1) is cast on a casting machine to obtain an Al casting sheet or a Cu casting sheet.
[0023] Preferably, in step 1), the casting slurry is prepared by ball-milling the metal powder, solvent and dispersant for 24 to 32 hours to obtain a premix, and then adding the binder and plasticizer to the premix and continuing to ball-mill for 24 to 32 hours to obtain the casting slurry.
[0024] Preferably, in step 1), the solvent is a mixture of anhydrous ethanol and butanone, and the mass ratio of the two is 0.9-1.1:1; the dispersant is Hypermer KD-1; the plasticizer is a mixture of dibutyl phthalate (DBP) and glycerol, and the mass ratio of the two is 0.1-0.3:1; and the binder is polyvinyl butyral (PVB).
[0025] Preferably, in step 1), in the casting slurry, the raw material components, by mass percentage, are: metal powder 45% to 54%, solvent 38% to 47%, dispersant 0.9% to 1.1%, plasticizer 3% to 4%, binder 3.4% to 3.9%, totaling 100%.
[0026] Preferably, in the step 2), the casting slurry is poured into the material trough of the casting machine, the scraper height is controlled to be 80-200 μm, the casting speed is 60-80 cm / min for casting, and then dried for 12-24 hours to obtain the cast sheet.
[0027] According to the above scheme, in step 2, the debinding sintering conditions are: debinding sintering is carried out in a protective atmosphere or a vacuum sintering furnace, first keeping the debinding temperature at 100-200°C for 2-3 hours, then gradually heating up to 300-350°C for 2-3 hours, then gradually heating up to 500-520°C for 1-2 hours, and then cooling to room temperature with the furnace and taking out.
[0028] According to the above scheme, in step 3, the sintering time is 2-3h.
[0029] According to the above scheme, in step 3, the sintering process is: first increase the temperature to 280-320°C, keep warm for 25-40 minutes, then increase the pressure to 290-300 MPa, and finally continue to increase the temperature to 485-500°C and keep warm for 2-3 hours.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The present invention provides an Al-Cu periodic laminated gradient composite material, in which a gradient material is obtained by alternately laminating Al layers and Cu layers with gradient thickness variations. The stacking design of pure components can more accurately construct a gradient structure, while reducing the mass transfer interface of aluminum and copper, making the interface bonding more stable. The obtained gradient material has the characteristics of high interface bonding strength, low intermetallic compound content, high interlayer flatness (bending degree less than 15 μm) and high density (up to 95.8%), which meets the research needs of material dynamic response under high strain rate and high pressure conditions, and provides a new material selection for the field of high stress and wide strain rate dynamic loading.
[0032] 2. The present invention provides a method for preparing Al-Cu periodic laminated gradient composite materials by using a tape casting method combined with a low-temperature sintering process. First, the tape casting method is used to obtain Al and Cu tape casting sheets with uniform thickness and smooth surface. After superposition, the binder is removed. Amorphous carbon will be introduced during the binder removal process. The amorphous carbon can be coated on the surface of the aluminum-copper powder, reducing the direct contact of the aluminum-copper interface and effectively inhibiting the diffusion of interface elements. Then, the appropriate temperature and pressure are coordinated to further reduce the element diffusion at the aluminum-copper interface, significantly reducing the risk of the formation of intermetallic compounds, while also ensuring the high density of the gradient composite material and achieving good metallurgical bonding at the interface. The laminated structure design further reduces the mass transfer interface of aluminum and copper, making the interface bonding more stable and the dynamic loading performance better. It has been verified by light gas gun experiments that the gradient material prepared by the present invention has high interlayer flatness, high strength, and excellent quasi-isentropic loading performance, showing a broad prospect for engineering application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a process flow chart of Example 1 of the present invention.
[0034] Figure 2 This is a schematic diagram of the structure of the periodic laminated gradient composite material designed in Example 1 of the present invention: Figure 2 a Gradient structure diagram; Figure 2 b is a schematic diagram of the gradient structure of the 14-layer aluminum-copper layer thickness ratio.
[0035] Figure 3 This is the sintering process used in hot pressing sintering in Example 1 of the present invention.
[0036] Figure 4is a microstructure diagram and energy spectrum diagram of the periodic laminated gradient composite material prepared in Example 1 of the present invention, wherein Figure 4 a is the microstructure diagram of functionally gradient materials, Figure 4 b and 4c are the energy spectra of the two elements Al and Cu in the functional gradient material.
[0037] Figure 5 This is the phase composition of the periodically laminated gradient composite material prepared in Example 1 of the present invention.
[0038] Figure 6 is a three-dimensional profile diagram of the periodic laminated gradient composite material prepared in Example 1 of the present invention, wherein Figure 6 a, 6b are Al surfaces, Figure 6 c, 6d are Cu surfaces.
[0039] Figure 7 This is the loading velocity waveform obtained by subjecting the periodically laminated gradient composite material prepared in Example 1 of the present invention to a first-stage light gas gun dynamic loading experiment. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the embodiments and drawings, but is not limited to the contents described below.
[0041] Example 1
[0042] A method for preparing an Al-Cu periodic laminate gradient composite material is provided, wherein the process flow is as follows: Figure 1 As shown, the specific steps include:
[0043] 1) Design structural parameters of periodic laminated gradient materials:
[0044] like Figure 2 As shown, the Al-Cu periodic laminated gradient composite material designed in this embodiment consists of 14 aluminum-copper composite layers plus a copper cap layer, the thickness of the aluminum-copper composite layer is a fixed value of 150μm, the composite layer consists of a layer of aluminum and a layer of copper, and the thickness of the aluminum layer plus the copper layer is 100%. From the first aluminum-copper composite layer to the last aluminum-copper composite layer, the thickness of the Al layer gradually decreases from 144.6μm to 5.4μm, while the thickness of the Cu layer gradually increases from 5.4μm to 144.6μm, and the last layer is a 312μm copper cap layer, with a total thickness of 2450μm.
[0045] The thicknesses of the Al layers from the first aluminum-copper composite layer to the fourteenth aluminum-copper composite layer are 144.6μm, 133.9μm, 123.2μm, 112.5μm, 101.8μm, 91.1μm, 80.4μm, 69.6μm, 58.9μm, 48.2μm, 37.5μm, 26.8μm, 16.1μm, and 5.4μm, respectively, and the rest are copper layers.
[0046] 2) Preparation of Al and Cu sheets by tape casting
[0047] The particle size of the aluminum powder is selected to be 1 to 3 μm; the particle size of the copper powder is selected to be 1 to 2 μm.
[0048] 9.5g aluminum powder, 0.22g Hypermer KD-1, 4.77g butanone, and 4.77g anhydrous ethanol were added to the zirconia ball mill in sequence, and the mixture was ball-milled for 24h on a three-dimensional planetary ball mill. Then, 0.7998g PVB, 0.08g DBP, and 0.665g propylene glycol were added to the primary slurry in sequence, and the mixture was ball-milled for 24h to obtain pure aluminum tape casting slurry. The steps were repeated to obtain pure copper tape casting slurry; the raw materials were 15g copper powder, 0.25g Hypermer KD-1, 5.375g butanone, 5.375g anhydrous ethanol, 0.95g PVB, 0.0998g DBP, and 0.876g propylene glycol.
[0049] Pour the prepared pure aluminum casting slurry or pure copper casting slurry into the material tank of the casting machine and control the scraper height to 80μm and the casting speed to 80cm / min to cast to obtain a casting sheet, and place the cast sheet in a drying cabinet to dry for 24h. That is, Al and Cu casting sheets are obtained.
[0050] 3) Preparation of gradient composite materials
[0051] The cast sheet after drying in step 2) is punched out with a round punch of 25 mm diameter. The punched aluminum sheets and copper sheets are alternately stacked according to the layer thickness structure designed in step 1) and placed in a WC mold. The binder is debonded in a vacuum atmosphere furnace. The atmosphere in the furnace is vacuum. The temperature is first kept at 200°C for 3 hours, then at 300°C for 2 hours, then raised to 510°C for 1 hour, and then cooled with the furnace.
[0052] Sinter the debinding sample, place the sample in the sintering mold, spray the demoulding agent on the contact point between the sample and the mold to facilitate demoulding after sintering. Place the mold in the hot press furnace for sintering, set the sintering temperature to 485℃ and the pressure to 300MPa. First, the temperature is raised to 300℃, and the temperature rise is paused for 30min. At this time, the pressure program is running, and the pressure is raised to 300MPa, and then the temperature is continued to rise to 485℃, and the temperature is kept for 2h. The sintering system is as follows: Figure 3 As shown, the heating rate is automatically set by the hot press furnace and is not taken into account. After the insulation is completed and the temperature is cooled down, the sample is taken out, which is the Al-Cu periodic laminated gradient composite material. The sample density is calculated by the Archimedes drainage method to be 95.8%.
[0053] Depend on Figure 4It can be seen that the periodic laminated gradient composite material prepared in the embodiment has a relatively high degree of parallelism between the internal layers, and the elements are evenly distributed. The Al layer and the Cu layer are alternately laminated as expected by the design. The thickness of the Al layer gradually decreases from the front end, and the thickness of the Cu layer gradually increases, gradually transitioning from more Al to more Cu, presenting a gradient structure.
[0054] Depend on Figure 5 It can be seen that the phase composition of the periodic laminated gradient material prepared in the embodiment is only aluminum and copper, and no other intermetallic compounds are generated.
[0055] Depend on Figure 6 It can be seen that the periodic laminated gradient material prepared in the embodiment has good surface flatness and a curvature below 15 μm.
[0056] Depend on Figure 7 It can be seen that the periodic laminated gradient material prepared in the embodiment is subjected to a first-level light gas gun experiment to obtain a target impact velocity waveform. At the beginning of loading, the slope of the free surface velocity curve rises sharply, and then the slope decreases. The elastic-plastic transition point is clearly visible, corresponding to point B. Subsequently, the free surface velocity rises sharply in a short period of time, with an initial jump similar in shape to a shock wave but with a relatively small amplitude, corresponding to the BC segment. This is due to the lower wave impedance of the pure Al layer at the front interface of the gradient composite material; followed by an up and down oscillating oblique wave loading stage, corresponding to the CD segment. This is because the target material will be subjected to a compression wave from the low impedance (AI) to high impedance (Cu) interface, which loads the flying flakes, and is also subjected to a sparse wave reflected from the high impedance (Cu) to low impedance (AI) interface, which unloads the flying flakes. The loading process involves the pursuit, superposition and integration of multiple wave systems to form a gradually increasing loading wave process, which is consistent with the stress wave superposition and integration loading process caused by the periodic gradient structure. The free surface velocity gradually increases and reaches a peak value. This process is called quasi-isentropic loading. After the velocity increases to the peak value, a peak platform CD segment appears. The interface reflected rarefaction wave reaches the interface of the material, causing the material velocity to decrease. The pulse duration during the entire loading process is 1.2μs, and the loading results are good, with a loading upward trend and a peak platform.
[0057] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. An Al-Cu periodic laminated gradient composite material, characterized in that: It includes n layers of Al-Cu composite layer and pure copper layer of the same thickness, wherein: The Al-Cu composite layer includes an Al layer and a Cu layer in sequence; and from the first Al-Cu composite layer to the nth Al-Cu composite layer, the thickness gradient of the Al layer decreases gradually, and the thickness gradient of the Cu layer increases gradually.
2. The gradient composite material according to claim 1, characterized in that: n is 5 to 20.
3. The gradient composite material according to claim 1, characterized in that: In the first Al-Cu composite layer, the thickness ratio of the Al layer to the Cu layer is 25-28:1, and in the last Al-Cu composite layer, the thickness ratio of the Al layer to the Cu layer is 1:25-28.
4. The gradient composite material according to claim 1, characterized in that: The thickness of a single Al-Cu composite layer is 130-170 μm, and the thickness of a pure copper layer is 300-1350 μm.
5. The gradient composite material according to claim 1 or 4, characterized in that: In the n-layer Al-Cu composite layer, the thickness of the Al layer decreases by 9 to 13 μm per layer, and the thickness of the Cu layer increases by 9 to 13 μm per layer.
6. A method for preparing the Al-Cu periodic laminated gradient composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Prepare Al and Cu cast films respectively by tape casting method, and then cut and demold to obtain the required Al and Cu cast sheets; Step 2: According to the structural design of the Al-Cu periodic laminated gradient composite material, the Al and Cu tape-cast sheets obtained in the multilayer step 1 are overlapped to form a gradient structure laminate, and then the binder is removed to obtain a gradient composite material blank; Step 3: The gradient composite material blank obtained in step 2 is pressed as a whole, and then hot-pressed and sintered at 290-300 MPa and 485-500° C. to finally obtain an Al-Cu periodic laminated gradient composite material.
7. The preparation method according to claim 6, characterized in that: In step 1, the specific process of preparing Al and Cu cast sheets by tape casting is as follows: 1) preparing a casting slurry containing metal powder, solvent, dispersant, binder and plasticizer by ball milling, wherein the metal powder is aluminum powder or copper powder; 2) The casting slurry obtained in step 1) is cast on a casting machine to obtain an Al casting sheet or a Cu casting sheet.
8. The preparation method according to claim 7, characterized in that: In the step 1), the raw material components in the casting slurry are calculated by mass percentage as follows: 45% to 54% metal powder, 38% to 47% solvent, 0.9% to 1.1% dispersant, 3% to 4% plasticizer, and 3.4% to 3.9% binder, which totals 100%.
9. The preparation method according to claim 7, characterized in that: In the step 1), in the casting slurry, the solvent is a mixture of anhydrous ethanol and butanone, and the mass ratio of the two is 0.9-1.1:1; the dispersant is Hypermer KD-1; the plasticizer is a mixture of dibutyl phthalate and propylene glycol, and the mass ratio of the two is 0.1-0.3:1; and the binder is polyvinyl butyral.
10. The preparation method according to claim 6, characterized in that: In step 2, the binder removal sintering conditions are: the binder removal sintering is carried out in a protective atmosphere or vacuum sintering furnace, firstly, the binder removal temperature is kept at 100-200°C for 2-3 hours, then gradually heated to 300-350°C for 2-3 hours, then gradually heated to 500-520°C for 1-2 hours, and then cooled to room temperature with the furnace and taken out; In step 3, the sintering process is: firstly, the temperature is raised to 280-320°C, kept at this temperature for 25-40 minutes, then the pressure is raised to 290-300 MPa, and finally the temperature is further raised to 485-500°C, kept at this temperature for 2-3 hours.